The situation of the Hungarian agricultural higher education - Magda , Sándor; Herneczky , Andrea; Marselek , Sándor; Varga, Erika (Applied Studies in Agribusiness and Commerce, 2009)
The knowledge-based, competitive economy places a great emphasis on the education system. The responsibility of higher education is to impart knowledge of high standard which is in harmony with the continuously changing environment. Higher education has a special role in the knowledge-based economy since it does not only have to fulfil educational but also research an innovation tasks. The decrease in the traditional role of agriculture as well as international tendencies facilitate diversification, i.e. the emergence of new roles and the relevant activities. Due to the diversification of agriculture fields like environmental protection, bioenergetics, and rural development have become more emphatic. The growing importance of these new fields is also significant from the point of view of education. Well trained professionals are of vital importance for the agriculture. A significant number of fresh graduates are not employed in their profession; they find a job in other areas or continue their education in a different field of interest. This research is based on a representative survey amongst agricultural graduates. Its objective is finding facts about how the graduates of the past five years assess higher education training and also about the factors employers take into consideration when employing a fresh graduate.